Penyuluhan Kewirausahaan Bagi Kelompok Umkm Guna Meningkatkan Motivasi Dalam Berwirausaha - Netri Rahma Yuliani (Jurnal Pengabdian UntukMu NegeRI, 2020)
In the village of Tarandam Nagari Siguntur Tua, there is a group of MSME. The community prefers to go to the garden to make a living for the family rather than participate in an activity that is not or less profitable and does not get money in return. Even though if the activities of MSME run optimally, the community can make it as a place for entrepreneurship by utilizing available natural resources, so as to improve the family's economy. Entrepreneurship is an additional alternative part of the activities of MSME so that it is more useful and has added value to families and communities in the Old Siguntur Old Age. So, it is necessary to provide motivation and foster entrepreneurial spirit to the MSME group in Old Agate Siguntur. Therefore, the writer as a student of Field Work Lectures from the Department of Education outside the School of Education at the State University of Padang is interested in discussing and providing alternative solutions to overcome these problems. This is applied to the community service with Entrepreneurship Counseling for MSME To Increase Motivation in Entrepreneurship in Tarandam Nagari Siguntur Tua Village, Tarusan District, South Coastal Province, West Sumatra Province.